Avaliação da aprendizagem de alunos com deficiência: estudo de caso em uma instituição de ensino superior da rede pública de Fortaleza-Ceará - Benevides, Marta Cavalcante (2011)
The learning evaluation for disabled students is a pedagogic element of great importance; it can aid or raise difficulties for these students’ educational inclusion. The inclusive avaluation must be prospective, accomplishing a diagnosis of the disabled students’ emerging cognitive conditions. Therefore, it should not be limited to the verification of their acquired capacities. That type of superficial evaluation seems to be harmful, because it can decrease the expectations of the professionals of Education, especially the teacher or professor, regarding that specific group. The educational inclusion of disabled students becomes, as a result, a challenge, because the daily practices of all the teaching levels are still very influenced by traditional conceptions of evaluation that exclude those students with differentiated ways of learning and living. The main purpose of the current research is to accomplish an investigation about the practice of learning evaluation for disabled students registered in graduate and postgraduate level courses of humanities and educational areas in a Public Institute of Higher Education. Specifically, this study aimed: i) knowing the difficulties lived by students, professors and coordinators regarding learning evaluation for disabled students; ii) identifying the accessibility conditions concerning the practices of learning evaluation; iii) gathering contributions of students, professors and coordinators for an inclusive practice of learning evaluation. Thus, a qualitative research was accomplished, as a case study. The semi-structured interview and the questionnaire were used as instruments for data collection. A content analysis of the collected data was accomplished. The sample was composed by: nine disabled students; seven graduate level course’s coordinators and nineteen professors; thirty five subjects altogether. The results revealed that the adaptations accomplished to evaluate the disabled student are still insufficient. The difficulties refer to an inadequate professor educational, to the lack of physical and structural adaptation and the absence of a larger discussion on the theme. The suggestions point to the importance of investment in material and human resources and the adaptation of physical spaces.